2020
DOI: 10.1371/journal.pone.0226792
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at the timecourse of mind wandering: Pupillary responses and behaviour

Abstract: Mind wandering (MW) refers to the shift of attention away from a primary task and/or external environment towards thoughts unrelated to the task. Recent evidence has shown that pupillometry can be used as an objective marker of the onset and maintenance of externally-driven MW episodes. In the present study we aimed to further investigate pupillary changes associated with the onset and duration of self-reported MW episodes. We used a modified version of the joint behavioural-pupillometry paradigm we recently i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 68 publications
(104 reference statements)
1
4
0
Order By: Relevance
“…Importantly, controlling for the effect of the button press showed that this effect was specific to the process of becoming aware of an ongoing distraction and not related to motor preparation. These results are also in line with Pelagatti and collaborators' study (2020) that showed that a larger pupil dilation preceded self-detected mind wandering episodes compared with on-task trials (Pelagatti et al, 2020). Finally, in terms of the LC-NE modes of activation, this type of activity resembles the phasic activation mode (Aston-Johnes & Cohen, 2005), typically associated with task-related, more significant cognitive effort.…”
Section: Discussionsupporting
confidence: 85%
“…Importantly, controlling for the effect of the button press showed that this effect was specific to the process of becoming aware of an ongoing distraction and not related to motor preparation. These results are also in line with Pelagatti and collaborators' study (2020) that showed that a larger pupil dilation preceded self-detected mind wandering episodes compared with on-task trials (Pelagatti et al, 2020). Finally, in terms of the LC-NE modes of activation, this type of activity resembles the phasic activation mode (Aston-Johnes & Cohen, 2005), typically associated with task-related, more significant cognitive effort.…”
Section: Discussionsupporting
confidence: 85%
“…Calculating the span length of low or high α trials for each listener showed averages of ∼ 1.7 trials in both hearing groups, equating to several hundred milliseconds during our task. The relative speed of these fluctuations suggests that the α-modulations observed here are unlikely related to mind wandering per se , which presumably develops over longer time courses [tens of seconds ( Pelagatti et al, 2020 )]. Instead, we infer low α power tracks a high arousal state while high α power reflects task focus but in a state of wakeful relaxation.…”
Section: Discussionmentioning
confidence: 89%
“…Calculating the span length of low-or high-α trials for each listener showed averages of ~ 1.7 trials in both hearing groups, equating to several hundred milliseconds during our task. The relative speed of these fluctuations suggests that the α-modulations observed here are unlikely related to mind wandering per se, which presumably develops over longer time courses [tens of seconds (Pelagatti et al, 2020)]. Instead, we infer low α power tracks high arousal state while high α power reflects task focus but in a state of wakeful relaxation.…”
Section: Effects Of Age On Cortical α Power and Cortical Modulation O...mentioning
confidence: 58%